Cultural Specifics of Management in Multinational Companies - Křečková Kroupová, Zuzana, 1972-; Pražská, Lenka; Zadražilová, Dana, 1958-; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2009)
Nowadays the world is becoming increasingly economically connected, and cultural diversity of employees is gaining importance as a crucial competitive advantage. Cross-cultural communication ability is becoming a key management skill in multinational firms and is equally important for other employees who are exposed to other cultures in the workplace. This work mainly focuses on cultural specifics of management in multinational firms. The goal of this thesis is to discover how different national cultures influence management of people, particularly work relationships, management tools and organization structures. The author discovers this through cultural dimensions that she updates for the Czech Republic and Slovakia for her work using methodology of Fons Trompenaars. The author tests three hypotheses: about the development of preferences of cultural dimensions in time, differences in preferences of cultural dimensions of Czechs and Slovaks and differences in preferences of cultural dimensions based on people's gender, age and the number of years spent abroad. The work also presents mapping of changes of attitudes in specific work and personal situations of Czechs and Slovaks over a period of time. The work additionally analyzes the influence of economic factors on work attitudes and preferences of cultural dimensions and identifies areas of potential conflicts between the cultures of Czechs and Slovaks in the workplace. It also compares results with other researches about cultural dimensions and cultural standards. The work concludes by presenting culturally specific recommendations for management of Czechs and Slovaks.
Vedoucí práce: Lenka Pražská
Disertační práce (Ph.D.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2009
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2009
Způsob přístupu: Internet
Keywords: mezinárodní ekonomické vztahy [obor disert. práce]; disertace; dissertations